(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, we will explore the intricate dynamics between climate change and land cover change in the Aral Sea of Uzbekistan. We will examine the historical context, the key drivers of change, and the ecological and socioeconomic consequences of these transformations. Furthermore, we will delve into the efforts being made to address the crisis, including international collaborations, policy interventions, and innovative restoration initiatives. By shedding light on the relationship between climate and land cover change in the Aral Sea, we hope to contribute to the ongoing dialogue on sustainable environmental management and resilience in the face of global environmental challenges